Burns infection profile of Singapore: prevalence of multidrug-resistant Acinetobacter baumannii and the role of blood cultures. Issue 1 (December 2016) - Song, Christopher; Hwee, Jolie; Song, Colin; Tan, Bien; Chong, Si
Abstract Background With various changes implemented such as perioperative antibiotics for tangential excision, this retrospective study reviews the infection profile of burn patients at Singapore's only centralized burns unit. Worldwide, the appearance of multidrug-resistant (MDR) strains ofAcinetobacter baumannii (A. baumannii ) continues to worsen patient outcomes. This study also surveys the role of blood cultures in burns at our unit. Methods Four hundred fifty-two burn patients admitted to the unit between 2011 and 2013, and with cultures performed, were included in the study. The yields of various cultures were evaluated and 2684 samples were amassed, of which 984 (36.7 %) were positive. Patient variables for predictors of MDRA. baumannii infection acquisition and bacteremia were evaluated through multivariate analyses. Results Pseuodomonas aeruginosa (P. aeruginosa ) (67 patients) was the most common organism in those with total body surface area (TBSA) burn <20 % while MDRA. baumannii ( 39 patients) was most prevalent in those with TBSA burn ≥20 %. We found a yield of 1.1 % positive blood cultures for TBSA burn <20 % and a yield of 18.6 % positive cultures in TBSA burn ≥20 %. The median time between surgery and bacteremia was 6.5 days (range -18 to 68 days, interquartile range 4.5); 2.9 and 8.8 % of bacteremic episodes occurred within 24 and 48 h, respectively. This is a decrease from a predeceasing study (45.3 % for 24 h and 60 % for 48 h). Multivariate analysis revealed that length of hospital stay and TBSA burn ≥20 % were predictors of MDRA. baumannii infection and positive blood cultures. Conclusions MDRA. baumannii infection burdens patient management, especially in those with TBSA burn ≥20 % and longer hospital stay. Prophylactic antibiotics may reduce perioperative bacteremia, but their role in MDR infections needs to be evaluated. The role of blood cultures in TBSA burn <20 % needs reconsideration.